2013
DOI: 10.2174/156652413804810745
|View full text |Cite
|
Sign up to set email alerts
|

The Caveolin-1 Connection to Cell Death and Survival

Abstract: Abstract:Caveolins are a family of membrane proteins required for the formation of small plasma membrane invaginations called caveolae that are implicated in cellular trafficking processes. In addition to this structural role, these scaffolding proteins modulate numerous intracellular signaling pathways; often via direct interaction with specific binding partners. Caveolin-1 is particularly well-studied in this respect and has been attributed a large variety of functions. Thus, Caveolin-1 also represents the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 144 publications
1
31
0
Order By: Relevance
“…Yet, additional mechanisms complicating the scenario have been described, since the inhibitory interaction of Cav-1 with the epidermal growth factor receptor can be hindered by the formation of a galectin-glycoprotein lattice, thereby resulting in sustained receptorial activity, as observed in breast tumor cells [60], [61]. Beyond functioning as a tumor suppressor, accumulating evidence have more recently indicated that Cav-1, especially when phosphorylated in Tyr14, behaves as an ambiguous partner in cancer [11][15], because of its ability to activate pathways involved in cell migration and invasion, such as the Rho/ROCK and Focal adhesion kinases signaling systems [62]. The data presented here point to pCav-1 as a positive modulator of proliferation, migration, invasiveness, chemoresistance in vitro and tumor growth in vivo in RMS, the most frequent childhood soft tissue sarcoma characterized by expression of myogenic markers and impaired differentiation [21][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, additional mechanisms complicating the scenario have been described, since the inhibitory interaction of Cav-1 with the epidermal growth factor receptor can be hindered by the formation of a galectin-glycoprotein lattice, thereby resulting in sustained receptorial activity, as observed in breast tumor cells [60], [61]. Beyond functioning as a tumor suppressor, accumulating evidence have more recently indicated that Cav-1, especially when phosphorylated in Tyr14, behaves as an ambiguous partner in cancer [11][15], because of its ability to activate pathways involved in cell migration and invasion, such as the Rho/ROCK and Focal adhesion kinases signaling systems [62]. The data presented here point to pCav-1 as a positive modulator of proliferation, migration, invasiveness, chemoresistance in vitro and tumor growth in vivo in RMS, the most frequent childhood soft tissue sarcoma characterized by expression of myogenic markers and impaired differentiation [21][28].…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1, in particular, has been shown to mostly inhibit a large number of signaling pathways because of the presence of a caveolin scaffolding domain that allows the binding of a plethora of proteins, such as epidermal growth factor receptor, protein kinases C, endothelial nitric oxide synthase [7]. In response to a variety of stimuli such as growth factors, UV irradiation, mechanical and oxidative stress, Cav-1 can also be phosphorylated on tyrosine 14 (hereafter referred as to pCav-1) by members of the sarcoma kinases (Src-kinases) [8]–[10], in turn leading to activation of pathways linked to cell death or survival [11]. In cancer, there is mounting evidence that pCav-1 occurrence often predicts unfavorable outcome by supporting anchorage-independent cell growth, migration, invasiveness and multidrug resistance [11][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIMK1 overexpression has been noted in breast cancer progression [39], while paxillin overexpression has been shown to enhance breast cancer metastasis [40]. Caveolin-1 is a scaffolding protein found in certain types of lipid rafts that facilitate cellular signal transduction [41]. Caveolin-1 has been shown to be positively influence many biological processes including cell migration and cell stress responses [41, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Caveolin-1 is a scaffolding protein found in certain types of lipid rafts that facilitate cellular signal transduction [41]. Caveolin-1 has been shown to be positively influence many biological processes including cell migration and cell stress responses [41, 42]. In fact, caveolin-1 is phosphorylated on tyrosine residues in response to cellular stress [42], and pTyr14-caveolin-1 is significantly upregulated in late/nulliparous women perhaps suggesting increased levels of cellular stress (Table 2, Figure 2D).…”
Section: Resultsmentioning
confidence: 99%